Neonates with Maternal Colonization of Carbapenemase-Producing, Carbapenem-Resistant Enterobacteriaceae: A Mini-Review and a Suggested Guide for Preventing Neonatal Infection - Judy Seesahai; Paige Terrien Church; Elizabeth Asztalos; Melanee Eng-Chong; Jo Arbus; Rudaina Banihani (MDPI AG, 2021)
Carbapenemase-producing, carbapenem-resistant Enterobacteriaceae (CP-CRE) are highly drug-resistant Gram-negative bacteria. They include New Delhi metallo-ß-lactamase (NDM)-producing carbapenemase (50.4% of all species in Ontario). Antibiotic challenges for resistant bacteria in neonates pose challenges of unknown dosing and side effects. We report two antenatally diagnosed CP-CRE colonization scenarios with the NDM 1 gene. The case involves extreme preterm twins who had worsening respiratory distress at birth requiring ventilator support, with the first twin also having cardiovascular instability. They were screened for CP-CRE, and a polymyxin antibiotic commenced. In the delivery room, neonatal intensive care unit (NICU) and the follow-up clinic, in collaboration with the interdisciplinary group, contact precautions and isolation procedures were instituted. None of the infants exhibited infection with CP-CRE. Consolidating knowledge with regard to CP-CRE and modifying human behavior associated with its spread can mitigate potential negative consequences. This relates to now and later, when travel and prolific human to human contact resumes, from endemic countries, after the current COVID-19 pandemic. Standardized efforts to curb the acquisition of this infection would be judicious given the challenges of treatment and continued emerging antibiotic resistance. Simple infection control measures involving contact precautions, staff education and parental cohorting can be useful and cost-effective in preventing transmission. Attention to NICU specific measures, including screening of at-risk mothers (invitro fertilization conception) and their probands, careful handling of breastmilk, judicious antibiotic choice and duration of treatment, is warranted. What does this study add? CP-CRE is a nosocomial infection with increasing incidence globally, and a serious threat to public health, making it likely that these cases will present with greater frequency to the NICU team. Only a few similar cases have been reported in the neonatal literature. Current published guidelines provide a framework for general hospital management. Still, they are not specific to the NICU experience and the need to manage the parents' exposure and the infants. This article provides a holistic framework for managing confirmed or suspected cases of CP-CRE from the antenatal care through the NICU and into the follow-up clinic targeted at preventing or containing the spread of CP-CRE.